Mengukur tingkat kemampuan struktur finansial dan modal terhadap profitabilitas pada perusahaan konstruksi di tengah pandemi - Nugraha, Fauzi Purwa; Munajat, MD Enjat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine or study the influence of financial structure and net working capital on the profitability of construction companies in companies listed on the IDX. Financial Structure and Net Working Capital as independent variables, and Profitability (ROE) as dependent variables. Financial Structure and Net Working Capital have no effect on Profitability either jointly or partially. The research was conducted on the company's financial statements for the quarterly period of 2020-2021 which were selected through purposive sampling technique, with the reason for the limitation of research by the company and the consideration that the report was still relevant to current economic conditions. The analytical method used in this research is Multiple Linear Regression Analysis. Hypothesis testing is done by using a significance level of 5%. From this research, it is found that Financial Structure and Net Working Capital together and partially have no significant effect on profitability